Respons pertumbuhan tanaman secang (Caesalpinia sappan L.) terhadap dosis pupuk kandang sapi - Muhammad Rizki Fauzan; Santi Rosniawaty; Yudhitia Maxiselly; Mira Ariyanti (Composite : Jurnal Ilmu Pertanian, 2024)
Sappan wood (Caesalpinia sappan L.) is a plant that contains the compound brazilin, which is found in the pith of its stem. The pith of the sappan wood stem can be used as a raw material for traditional medicine or as a dye with red pigment. Currently, there are no procedures or guidelines for cultivating techniques for sappan wood plants. Each annual plant requires a certain amount of organic material at the beginning of planting to support its growth. The organic material commonly used is manure, one of which is cow manure. This research aims to determine the effect of cow manure dosage on the growth of sappan plants. The experiment was conducted from March 2023 to December 2023 at Ciparanje Research Center, Faculty of Agriculture, Universitas Padjadjaran. The method used is experimental by design Randomized Block Design consisting of three treatments namely, it was repeated six times: 1 kg cow manure/plant, 2 kg cow manure/plant, and 3 kg cow manure/plant. The experimental results showed that treatment with 2 kg cow manure/plant had the best effect on plant height at 5,6,7,8, and 9 months after treatment (MAT) and the number of leaves at 5 and 9 MAT. There has been no response in plant diameter to the dose of cow manure fertilizer